2016
DOI: 10.1177/1357633x16637725
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the preferences of older people for telehealth as a new model of health care service delivery: A discrete choice experiment

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 79 publications
2
70
0
Order By: Relevance
“…Telerehabilitation can eliminate the need for travel, leading to considerable cost-and time-savings for patients (Levy, Silverman, Jia, Geiss, & Omura, 2015) and thus may potentially address the needs of those who are unwilling or unable to travel to physical therapy clinics in-person. This might include people who have limited time, live in a remote area, lack transportation, or have disabling conditions that make it difficult to attend clinics in-person (Kaambwa et al, 2017;Ward, Schmidt, Lappan, & Battafarano, 2016). For clinicians, the increased convenience and accessibility of telerehabilitation means that they can potentially reach a wider range of clientele who may otherwise be unable to attend clinics in-person (Lawford, Delany, Bennell, & Hinman, 2018a).…”
Section: Technology Provide S Opp Ortunitie S For Remotely-deliverementioning
confidence: 99%
“…Telerehabilitation can eliminate the need for travel, leading to considerable cost-and time-savings for patients (Levy, Silverman, Jia, Geiss, & Omura, 2015) and thus may potentially address the needs of those who are unwilling or unable to travel to physical therapy clinics in-person. This might include people who have limited time, live in a remote area, lack transportation, or have disabling conditions that make it difficult to attend clinics in-person (Kaambwa et al, 2017;Ward, Schmidt, Lappan, & Battafarano, 2016). For clinicians, the increased convenience and accessibility of telerehabilitation means that they can potentially reach a wider range of clientele who may otherwise be unable to attend clinics in-person (Lawford, Delany, Bennell, & Hinman, 2018a).…”
Section: Technology Provide S Opp Ortunitie S For Remotely-deliverementioning
confidence: 99%
“…Discrete choice experiments (DCEs) offer a way of eliciting preferences for the characteristics or attributes of an intervention; they also provide information on the trade‐offs (the decision to sacrifice the benefits of one attribute in favour of another) that respondents are prepared to make between attributes. DCEs have been used in health‐care settings to improve the design and delivery of patient services . Their use also extends to cancer screening programmes; a systematic review identified 22 stated preference studies published between 1990 and 2013 addressing breast, cervical and colorectal cancer screening …”
Section: Introductionmentioning
confidence: 99%
“…Patient viewpoints are important. Kaambwa et al 34 found in their study of older people that patients had strong preference for telehealth services that targeted individuals living in remote regions without easy access to clinic. Our previous research 16 demonstrated that distance to travel to a hospital was not the sole reason leading to the acceptability of Skype consultations and that preference is multifactorial.…”
Section: Discussionmentioning
confidence: 99%